(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2011)
Organicâ€“inorganic hybrid sample NH3(C6H4)2NH3HgCl4 was characterized by differential scanning calorimetry (DSC), TGA analysis and electrical impedance spectroscopy. DSC studies indicated the presence of a one-phase transition at 391 K. As for the ac conductivity of the compound NH3(C6H4)2NH3HgCl4, it has been measured in the temperature range of 358 - 413K and the frequency range of 209 Hzâ€“5 MHz. Concerning the Zâ€™ and Zâ€™â€™ versus frequency plots, they were well-fitted to an equivalent circuit model. The equivalent circuit is composed of a series of combination of two parallel (R//CPE) circuits. Besides, the frequency dependence of the conductivity was interpreted in terms of Jonscher’s law Ïƒ(Ï‰) = Ïƒdc +A Ï‰n. Â As regards the conductivity, it follows the Arrhenius relation. The variation of the value of the conductivity with temperatures confirmed the availability of the phase transition at 391K detected by DSC and electrical measurements.